Legitimacy, institutional trust, and political moral laxity: psychopolitical impact of the governance of the legacy of ‘Lima 2019’ games - Martí, Jordi; Cueto, Rosa María; Espinosa, Agustín (Frontiers in Political Science, 2025)
This paper analyzes the relationships between the perception of legitimacy, institutional trust, and political moral laxity (PML) using “Proyecto Especial Legado” (LEGADO) as a case study. LEGADO is a public governance organization, created by the Government of Peru to manage the infrastructure and provide services derived from the organization of the Pan American and Parapan American Games “Lima 2019.” The results indicate a direct relationship between the perception of LEGADO’s objectives fulfillment (as an indicator of legitimacy) and the positive approval of this organization (as an indicator of institutional trust). Conversely, PML negatively affects approval for LEGADO. However, this relationship is mitigated when the perception of objectives fulfillment is introduced as a mediating variable. Thus, although the effects are limited, a positive perception of objectives fulfillment may help reduce the adverse effects of PML on trust in LEGADO. To conduct this research, a correlational study was performed using data collected from a questionnaire administered to 404 citizens in the Lima Metropolitan Area, which addressed issues of legitimacy, institutional trust, and PML in relation to the public governance of the games and their legacy (through LEGADO). Finally, the implications of a governance legitimized by the fulfillment of institutional objectives are discussed, particularly regarding its impact on breaking the vicious cycle that links PML with institutional distrust.